Wolf wanted - Machado, Ana Maria, 1941- (Groundwood Books/House of Anansi Press, 2010)
Manny Wolf rewrites a help wanted ad, clarifying that a real wolf is needed so that a documentary can be made to show people what real wolves are like and how different they are from their big, bad fictional counterparts who've applied for the job.